2008
DOI: 10.1210/en.2008-0433
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Activational Effects of Testosterone on Masculinization of Female Physiological and Behavioral Stress Responses

Abstract: The prevalence of affective disorders is two times greater in women than in men. The onset of anxiety and depression occurs at different ages that may correspond to key developmental periods when the brain is more vulnerable to hormonal and exogenous influences. Because stressful life events can precipitate disease onset, the development of greater stress sensitivity in females may contribute to their increased vulnerability. Gonadal hormone exposure in males during early development and again from puberty onw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 65 publications
8
76
0
Order By: Relevance
“…Sex differences in stress sensitivity are often attributed to differences in HPA axis function (Bangasser and Valentino, 2012;Handa et al, 1994). Indeed, our results confirm previous reports showing that females generally have higher resting levels of corticosterone, and have a more pronounced increase in corticosterone secretion in response to stress (Goel and Bale, 2008;Handa et al, 1994). However, we demonstrate here that the rapid changes in gene expression in response to stress are not mediated by corticosterone.…”
Section: Discussionsupporting
confidence: 91%
“…Sex differences in stress sensitivity are often attributed to differences in HPA axis function (Bangasser and Valentino, 2012;Handa et al, 1994). Indeed, our results confirm previous reports showing that females generally have higher resting levels of corticosterone, and have a more pronounced increase in corticosterone secretion in response to stress (Goel and Bale, 2008;Handa et al, 1994). However, we demonstrate here that the rapid changes in gene expression in response to stress are not mediated by corticosterone.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, adult sex differences in hippocampal expression of the glucocorticoid receptor, critical for the negative feedback and modulation of the HPA stress axis, was disrupted in females masculinized at birth by a single injection of testosterone, supporting the importance of the male testosterone surge in normal wiring of sex differences in stress pathways (Bingham and Viau, 2008;Goel and Bale, 2008;Goel et al, 2011). In addition to this early critical period of programming, the rise in gonadal hormones beginning in puberty interacts with these organizational changes and exerts modulatory actions on neurotransmitter systems critical in regulation of sex differences in stress responsivity.…”
Section: Sex Differences Related To Sex Chromosomes and Hormones And mentioning
confidence: 98%
“…This variability comparison has now similarly been completed in rats as well . In addition, many behavioral studies have similarly reported that when estrous cycle stage was included as a variable, no significant differences in outcome measures were found, including for the Barnes maze, tail suspension test, forced swim test, elevated plus maze, light-dark box, and open-field tests (Mueller and Bale, 2007;Goel and Bale, 2008;Goel and Bale, 2009;Goel and Bale, 2010;Goel et al, 2011). This is not to say that gonadal hormones are not important in behavioral responses, but rather that the variability within females when comparing their outcomes to males does not explain sex differences.…”
Section: Sex As a Biological Variable Tl Bale And Cn Eppersonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have found that in this test, female rats in prooestrous are more sensitive to diazepam, than male and female rats in dioestrous (Fernandez-Guasti and Picazo, 1990). Finally, in a study where the marble burying test was used as an anxiety model, female rats tended to bury fewer objects than male rats (Goel and Bale, 2008).In another model of OCD, the deer mice, which are characterized by stereotypical behaviours, mice of both sexes have been used but no sex differences have been reported to date (Korff et al, 2008). With regard to genetic models, male ArKO mice, which lack oestrogens, show enhanced OCD-like behaviours, such as grooming and wheel running, whereas females do not (Hill et al, 2007).…”
mentioning
confidence: 88%